Mapping crop evapotranspiration with high-resolution imagery and meteorological data: insights into sustainable agriculture in Prince Edward Island - Imtiaz, Fatima; Farooque, Aitazaz; Wang, Xander; Abbas, Farhat; Afzaal, Hassan; Esau, Travis; Acharya, Bishnu; Zaman, Qamar (Frontiers in Remote Sensing, 2023)
Soil moisture variability caused by soil erosion, weather extremes, and spatial variations in soil health is a limiting factor for crop growth and productivity. The variability in crop water requirements at various growth stages is a common concern on a global level. In Canada's Prince Edward Island (PEI), where agriculture is particularly prominent, this concern is predominantly evident. The Island's most prominent business, agriculture, finds it challenging to predict agricultural water needs due to shifting climate extremes, weather patterns, and precipitation patterns. Thus, accurate estimations for irrigation water requirements are essential for water conservation and precision farming. This work used a satellite-based normalized difference vegetation index (NDVI) technique to simulate the crop coefficient (Kc) and crop evapotranspiration (ETc) for field-scale potato cultivation at the various crop growth stages for the growing seasons of 2021 and 2022. The standard FAO Penman-Monteith equation was used to estimate the reference evapotranspiration (ETr) using weather data from the nearest weather stations. The findings showed a statistically significant (p<0.05) positive association between NDVI, and tabulated Kc values extracted from all three satellites (Landsat 8, Sentinel-2A, and Planet) for the 2021 season. However, the correlation weakened in the subsequent year, particularly for Sentinel-2A and Planet data, while the association with Landsat 8 data became statistically insignificant (p>0.05). Sentinel-2A outperformed Landsat 8 and the Planet overall. The Kc values peaked at the halfway stage, fell before the maturity period, and were at their lowest at the start of the season. A similar pattern was seen for ETc (mm/day), which peaked at midseason and decreased with each developmental stage of the potato crop. Similar trends were seen for ETc (mm/day), which peaked at the mid-stage with mean values of 4.0 (2021) and (3.7), was the lowest in the initial phase with mean values of 1.8 (2021) and 1.5 (2022) and grew with each developmental stage of the potato crop. The study's ET maps show how agricultural water use varies throughout a growing season. Farmers in Prince Edward Island may find the applied technique helpful in creating sustainable growth plans at different phases of crop development.